The Adverb - Miss Grace of the elegance of our identity (JOURNAL OF ADVANCES IN LINGUISTICS, 2015)
A human being transcends into the world of continuous existence from the moment when he enters and is correctly oriented to engage himself to the work of self-awareness like a plenary-potential value creating of new values. He (human being) continuously feels the need of awareness/ self-exteriorization, especially the necessity of expression of his congenital- divinatory abilities. Otherwise, the externalization of oneself, as a formative purpose to the scale of divination, marks from the beginning the perspective of his optimal performances. And, if we are saying that the being is language, then we have to recognize the unanimity of the interpretative functions. The functions of interpretative art of the Moldovan Romanian peoples genius were always Messianic ones - of formatting an ideal Temple between the two enigmas: L. Blagas format - MAN, Horizon of Mysteries and ours MAN, Horizon of Great Virtues.